Compositional tuning, crystal growth, and magnetic properties of iron phosphate oxide - Tarne, Michael, author; Neilson, James, advisor; Shores, Matthew, committee member; Ross, Kate, committee member (Colorado State University. Libraries, 2017)
Iron phosphate oxide, Fe3PO4O3, is a crystalline solid featuring magnetic Fe3+ ions on a complex lattice composed of closely-spaced triangles. Previous work from our research group on this compound has proposed a helical magnetic structure below T = 163 K attributed to J1-J2 competing interactions between nearest-neighbor and next-nearest-neighbor iron atoms. This was based on neutron powder diffraction featuring unique broad, flat-topped magnetic reflections due to needle-like magnetic domains. In order to confirm the magnetic structure and origins of frustration, this thesis will expand upon the research focused on this compound. The first chapter focuses on single crystal growth of Fe3PO4O3. While neutron powder diffraction provides insight to the magnetic structure, powder and domain averaging obfuscate a conclusive structure for Fe3PO4O3 and single crystal neutron scattering is necessary. Due to the incongruency of melting, single crystal growth has proven challenging. A number of techniques including flux growth, slow cooling, and optical floating zone growth were attempted and success has been achieved via heterogenous chemical vapor transport from FePO4 using ZrCl4 as a transport agent. These crystals are of sufficient size for single crystal measurements on modern neutron diffractometers. Dilution of the magnetic sublattice in frustrated magnets can also provide insight into the nature of competing spin interactions. Dilution of the Fe3+ lattice in Fe3PO4O3 is accomplished by substituting non-magnetic Ga3+ to form the solid solution series Fe3-xGaxPO4O3 with x = 0, 0.012, 0.06, 0.25, 0.5, 1.0, 1.5. The magnetic susceptibility and neutron powder diffraction data of these compounds are presented. A dramatic decrease of the both the helical pitch length and the domain size is observed with increasing x; for x > 0.5, the compounds lack long range magnetic order. The phases that do exhibit magnetic order show a decrease in helical pitch with increasing x as determined from the magnitude of the magnetic propagation vector. This trend can be qualitatively reproduced by increasing the ratio of J2/J1 in the Heisenberg model. Intriguingly, the domain size extracted from peak broadening of the magnetic reflections is nearly equal to the pitch length for each value of x, which suggests that the two qualities are linked in this unusual antiferromagnet. The last chapter focuses on the oxyfluoride Fe3PO_7-xFx. Through fluorination using low-temperature chimie douce reactions with polytetrafluoroethylene, the magnetic properties show changes in the magnetic susceptibility, isothermal magnetization, and neutron powder diffraction. The magnetic susceptibility shows a peak near T = 13 K and a zero field cooled/field cooled splitting at T = 78 K. The broad, flat-topped magnetic reflections in the powder neutron diffraction exhibit a decrease in width and increase in intensity. The changes in the neutron powder diffraction suggest an increase in correlation length in the ab plane of the fluorinated compound. Iron phosphate oxide is a unique lattice showing a rich magnetic phase diagram in both the gallium-substituted and fluorinated species. While mean-field interactions are sufficient to describe interactions in the solid solution series Fe{3-xGaxPO4O3, the additional magnetic transitions in Fe3PO7-xFx suggest a more complicated set of interactions.
Keywords: magnetism; frustration